JOURNEY AND LIFE PUROPOSE IN ALEPH BY PAULO COELHO - Soendayana, Jessica Nathary Thenny (2016)
This research paper entitled "Journey and Life Purpose in Aleph by Paulo Coelho" aimed to analyze the kinds of journey presented in the selected novel and the way in which shape the main character's life purpose. Using a descriptive qualitative method, this study employs content analysis approach which is framed with theory from Bodart, Barrineau, and Flamino (2011) to interpret and understand the journey in the selected novel. The findings show that there are two kinds of journey presented in the novel, which are literal and metaphorical journey. Through his literal and metaphorical journey, the main character achieves his life purpose of spirituality and self-transcendence. From findings, it can be seen that journey is considered as an essentials process of life to be experienced by people. ;--- Penelitian yang berjudul "Journey and Life Purpose in Aleph by Paulo Coelho" ini bertujuan untuk menganalisis jenis perjalanan dan bagaimana perjalanan tersebut membentuk tujuan hidup karakter utama di dalam novel. Teori konten analisis yang diambil dari Bodart, Barrineau, dan Flamino (2011) merupakan bagian dari metode deskriptif kualitatif yang digunakan untuk menginterpretasi dan memahami makna dari sebuah perjalan dalam novel tersebut. Hasil dari penelitian ini menunjukan bahwa terdapat dua jenis perjalanan di dalam novel, yaitu perjalanan literal dan metafora. Melalui perjalanan literal dan metafora, karakter utama mencapai tujuan hidupnya dalam hal spiritual dan perbaikan diri. Dari hasil penelitian ini, dapat terlihat bahwa melakukan suatu perjalanan merupakan proses yang penting dalam hidup yang harus dialami oleh manusia.